The Philippines from c. 14,000 to 4,000 cal. BP in Regional Context - Pawlik, Alfred F (Archīum Ateneo, 2019)
In this paper, we review the current Philippine archaeological record between c. 14,000 and 4000 cal. BP in the context of our developing understanding of human adaptation to post-glacial environments at the end of the Pleistocene, and the cultural and technological changes that were occurring across Southeast Asia during this period. Due to their location at the northwestern fringes of Wallacea, close proximity to Borneo and Taiwan, and the long Palawan coastline bordering the southern margins of the South China Sea, the Philippines have likely acted as a conduit for the movements of people, material culture and ideas between the islands of Southeast Asia throughout prehistory. Current research suggests that the Philippines were possibly embedded in larger maritime networks from the Late Pleistocene onwards. This appears to have been a period of significant social change and technological innovation, as illustrated by the appearance of new organic and inorganic technologies and the emergence of diverse burial traditions across Southeast Asia. These included sophisticated fishing strategies, techniques of hafting and composite tool production, and long-distance interaction across the Philippine archipelago and Island Southeast Asia perhaps as far as Near Oceania.